2021
DOI: 10.33603/publika.v9i2.6724
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Media Digital Dalam Meningkatkan Promosi Dan Informasi Di Universitas Swadaya Gunung Jati Cirebon

Abstract: Perkembangan zaman yang semakin modern mendorong perubahan baik secara langsung maupun tidak langsung, meningkatnya jumlah pengguna internet sendiri telah menarik berbagai macam bisnis untuk mempromosikan produknya di internet. Pada dasarnya media sosial telah mengubah cara konsumen berinteraksi dan perusahaan di dalam memasarkan produk. Digital Media adalah media yang tersaji secara online. Pada tahun 2020-2022 terdapat pertambahan jumlah mahasiswa pada Univresitas Gunung Jati, padahal sedang terjadi pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Based on measurements taken on 120 respondents, it was found that from several social media used for promotion, website media showed very significant results. This means that new students at Gunung Jati University get campus information through the website, and the website has proven to be effective for use as a media for promotion and information dissemination (Wulandari, Heryani, & Nurlia, 2021). The effectiveness of using the website was also proven by Mardian Herri Pratama et al for promotional media in the East Surabaya Village, Kec.…”
Section: Introductionmentioning
confidence: 97%
“…Based on measurements taken on 120 respondents, it was found that from several social media used for promotion, website media showed very significant results. This means that new students at Gunung Jati University get campus information through the website, and the website has proven to be effective for use as a media for promotion and information dissemination (Wulandari, Heryani, & Nurlia, 2021). The effectiveness of using the website was also proven by Mardian Herri Pratama et al for promotional media in the East Surabaya Village, Kec.…”
Section: Introductionmentioning
confidence: 97%
“…In the end, people will decide to send their children to school. Furthermore, marketing educational services through digital media is very effective in increasing promotion and information, especially websites becoming the main portal and using official social media of educational institutions (Wulandari et al, 2022). Likewise, Islamic education marketing must use innovation through the marketing of educational services to compete in the digital era and affect the existence of educational institutions (Halim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%